Análise da amplitude da resposta das emissões otoacústicas e das latências das ondas do PEATE, como possíveis indicadores de comprometimento das células ciliadas cocleares e nervo auditivo, em lactentes com asfixia - Ribeiro, Georgea Espindola [UNESP] (2015)
Introduction: The integrity of the peripheral and central auditory system is essential to the intellectual and cognitive development. Therefore, hearing is a prerequisite for language acquisition and development. There is a number of risk factors for hearing loss, such as the index of low Apgar score and perinatal asphyxia, which is defined as an injury suffered by the newborn when there is significant tissue hypoperfusion and decreased oxygen supply resulting from various etiologies in the peripartum period. The universal neonatal hearing screening (UNHS) is intended to detect newborns with hearing loss as early as possible, especially those who present risk factors, through electroacoustic and electrophysiological procedures. From these, the most used ones are the transient-evoked otoacoustic emissions (TEOEs) and the evoked auditory brainstem response (EABR). Objective: Check the effect of low apgar score and of perinatal asphyxia in the responses of TEOEs and in the latencies of EABR. Method: 181 infants born at term who were seen in the UNHS program at the hospital of Botucatu Medical School participated in the study. They had the TEOEs exam with the result pass in both ears and EABR with absolute and interpeak latency values. They were divided into 3 groups: G1 with 20 infants who had perinatal asphyxia, G2 with 111 infants who presented only low Apgar score at birth, and G3 with 50 infants who had Apgar index at 1 e 5 minutes≥7. Results: The amplitudes of the TEOEs in the records of G3 had higher values when compared to those of G1 and G2 mainly at the frequency 4 kHz in male infants. No differences were found in the female infants. In the male infants, increased latency of waves I and III bilaterally was observed in group G1. Conclusion: The amplitude response was reduced in the newborns who had asphyxia or low Apgar score at birth, which shows the importance of intrinsic analysis of the TEOEs exam. The ...